Online learning instructional design facilitating participation, engagement, and interaction at a Higher Educational Institution in South Africa - Monyau, Thabiso Rantoana Ivan (University of the Witwatersrand, Johannesburg, 2022)
Online learning is now a practical alternative to traditional methods of instruction for access to education. This mode of instructional delivery comes with adaptations in both teaching and learning, and it demands stable access to digital resources and technological skills. Universities in developing countries like South Africa are still striving to adopt and adapt to new ways of providing education due to lack of capacity and shortage of Information and Communication Technology (ICT) infrastructure. This study aimed to investigate what informs the online learning instructional design of two online courses offered in a South African university to facilitate students’ and facilitators’ Participation, engagement, and Interaction (PEI). The inductive approach was used to collect and analyse data for this study that adopted case-study research strategy. Facilitator interviews, document analyses, and questionnaires issued to students were used as research instruments. The findings suggested that, the way in which the instruction is designed for online learning determines students’ and facilitators’ PEI, and students’ and facilitators’ PEI impact directly on the learning outcomes. Students’ and facilitators’ PEI also redirect learning to social activity of knowledge construction. On this basis, learning communities, collaboration and discussion play a pivotal role in facilitating students’ and facilitators’ PEI for online courses. Feedback and reflection were found as excellent ways to facilitate students’ and facilitators’ PEI that encourage the sharing of knowledge.” However, learner isolation remains a challenge, especially with large online classes and students that lack technological background.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Education (in the field of Educational Technology), to the Faculty Of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2022.
Keywords: Online learning; Instructional design; Learning communities; Participation; Engagement; Interaction; UCTD; SDG-4: Quality education